Analisis Strategi Pemasaran Air Minum Untuk Menjangkau Pasar Menggunakan Metode SWOT - Khoirudin, Khoirudin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. Dalwa Anugrah Hasaniyah is a bottled drinking water company under the auspices of the Dalwa Islamic boarding school. This company can be said to be a new company, therefore it needs to market its products effectively and efficiently. To achieve effective and efficient marketing, a marketing analysis is carried out. This analysis aims to analyze the strategies applied to the PT. Dalwa Anugrah Hasaniyah business as well as formulate new strategies by considering internal and external factors and determining alternative strategies that should be prioritized. The research method used is descriptive qualitative with analysis techniques using the IFAS-EFAS matrix, IE matrix, and SWOT matrix. The results of the analysis show that the Dalwa Anugrah Hasaniyah company is in the Grow and Build position so that the best strategy is to maintain and continue to innovate. The results of the SWOT recommendations, the company must read the market situation, establish cooperative relationships between agencies or governments, and sponsorship at events that require bottled drinking water.